Fundamentals of Entrepreneurship ENT 300 : D'4 Amigos / Bernedict Ready Babu ... [et al.] - Babu, Bernedict Ready; Joel, Julies; Lagang, Wenny; Sulaiman, Nurul Ezzah (2019)
D'4 Amigos offer a fresh honey from a log of stingless bee. We provide honey stick in order to give high satisfaction of customer and promote healthy food from agriculture industry. Our business is using a 4P’s marketing mix strategy. Firstly, we used price strategy to attract customer. By using this strategy, we offered a lower price for our product where our honey stick is priced RM 2 per 3 stick. It is because before we start to sold our product, we have some survey to our customer which is to help us to more understand about their ability or willingness to buy at a price that we set it up. Next, is product. Our product is fresh from a log of stingless bee. As we know, nowadays people more prefer to maduasli than madukelulut. But, for a information madukelulut also has more benefit and give us more healthy. Our product is free from chemical used. We were very concerned about our customer wants. We target among teenager as we promote to them about agriculture food. Also, not forget to the adult around this city. For promotion, we have promotes our product on online. We use Instagram as our medium to us to introduce our product. People who want to buy our honey stick, can directly book on our Instagram. We have packed our product on a jar if they want book honey stick more than 20 stick. In our packing also has Halal logo to give more safety and give trust to our customer. Lastly, place. We have choose Sibu as our place to sell and produce our product to customer. It is because Sibu has more 247995 populations which is among teenager and adult. In order to attract customer, we have to begin from a bottom because we know madukelulut is not really popular among us. But we believe, slowly people will able to try our product and we also can promote agriculture food as we an agricultural student.